Physical Characteristics and Shelf Life Estimation Of Instant Powder Drink Made from The Combination Of Yellow Sweet Potatoes and Red Beans - Chaidir Masyhuri Majiding; Muhammad Nuzul Azhim Ash Siddiq; Fahrul Rozi (Universitas Islam Negeri Alauddin Makassar, 2023)
Introdiction: In this modern era, people demand everything fast and practical. Likewise, in terms of food or beverage, people tend to prefer instant products. Instant products are food or beverage products that are easy to serve or consume in a relatively short time, such as instant powdered drinks. The physical characteristics of instant products can be interpreted as the essential properties of their ingredients in addition to chemical and biochemical properties. The physical characteristics are needed to develop instant products that are useful for producing quality food or beverage products. Aims: Instant powder drink product from the combination of yellow sweet potatoes and red beans need to be analyzed for their physical characteristics through yield, water absorption, solubility, viscosity, and shelf life. Result: The results of the analysis showed that the instant powder drink product combination of yellow sweet potato and red bean had a yield of 30.40%, a water absorption capacity of 4.98 ml, a solubility of 63.42%, and a viscosity of 14.80 cp. At the same time, the shelf life of this product is based on the assumption of average storage temperature in Indonesia (around 28ÂºC-38ÂºC), which is approximately 5 months of shelf life. Conclusion: Based on the results of the analysis, instant powder drink products have fairly good product stability and the product can be stored at room temperature or refrigerator